A cold-active esterase enhances mesophilic properties through Mn2+ binding - Marchetti, A; Orlando, M; Mangiagalli, M; Lotti, M (The FEBS Journal, 2023)
A key aspect of adaptation to cold environments is the production of cold-active enzymes by psychrophilic organisms. These enzymes not only have high activity at low temperatures, but also exhibit remarkable structural flexibility and thermolability. In this context, the role of metal ions has been little explored, and the few available studies seem to suggest that metal binding counteracts structural flexibility. This article reports an investigation into the role of the binding of manganese ion (Mn2+) in the thermal adaptation of an esterase (M-Est) of the GDSx family, identified in the genome of the Antarctic bacterium Marinomonas sp. ef1. M-Est is specific for esters containing acetate groups and turned out to be a highly thermolabile cold-active enzyme, with a catalysis optimum temperature of 5 °C and a melting temperature of 31.7 °C. A combination of biochemical and computational analyses, including molecular dynamics simulations, revealed that M-Est binds Mn2+ ions via a single binding site located on the surface of the enzyme, close to the active site. Although the interaction between M-Est and Mn2+ induces only local conformational changes involving the active site, quite surprisingly they trigger an improvement in both thermal stability and catalytic efficiency under mild temperature conditions. These results, together with the conservation of the Mn2+ binding site among psychrophilic and psychrotolerant homologues, suggest that Mn2+ binding may be a useful, albeit atypical, strategy to mitigate the detrimental effects of temperature on true cold-active enzymes.